Respuesta :

Answer:

2x+3y-5=0

Step-by-step explanation:

m=(y2-y1)/(x2-x1)

m=(3-(-1))/(-2-4)

m=(3+1)/-6

m=4/-6

simplify

m=-2/3

y-y1=m(x-x1)

y-(-1)=-2/3(x-4)

y+1=-2/3x+8/3

y=-2/3x+8/3-1

y=-2/3x+8/3-3/3

y=-2/3x+5/3

y-(-2/3x)=5/3

y+2/3x=5/3

3(y+2/3x)=3(5/3)

3y+6/3x=15/3

3y+2x=5

2x+3y=5

2x+3y-5=0

Answer:

2x + 3y - 5 = 0

Step-by-step explanation:

hello :

(4;-1) :   x=4 and y = -1     so : 2(4)+3(-1)-5 = 0    means : 8-3-5 =0...true

(-2;3) :   x=-2 and y = 3     so : 2(-2)+3(3)-5 = 0    means : -4+9-5 =0...true